2008
DOI: 10.1007/s10903-008-9146-2
|View full text |Cite
|
Sign up to set email alerts
|

Health Status of Mexican-Origin Persons: Do Proxy Measures of Acculturation Advance our Understanding of Health Disparities?

Abstract: U.S.-born Mexican-Americans have higher morbidity and mortality compared to Mexico-born immigrants. Mexico has lower healthcare resources, life expectancy, and circulatory system and cancer mortality rates, but similar infant immunization rates compared to the U.S. Along the U.S.-Mexico border, the population on the U.S. side has better health status than the Mexican side. The longer in the U.S., the more likely Mexican-born immigrants engage in behaviors that are not health promoting. Conclusions Researchers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 107 publications
2
50
0
Order By: Relevance
“…The significantly lower rates of gastroschisis among foreign-born women concord with many studies that have observed similarly paradoxical findings of better birth outcomes among foreign-born women, who are typically medically underserved and of lower socioeconomic status. Women born outside the U.S., particularly those of Hispanic ethnicity, have a lower risk of preterm delivery, low birth weight, and infant mortality, and they report less preterm labor and hypertension than U.S.-born women; this advantage tends to diminish with increasing acculturation (Cervantes et al, 1999;Crump et al, 1999;Buekens et al, 2000;Carter-Pokras et al, 2008;McDonald et al, 2008;Ruiz et al, 2008). The protective effect associated with being foreign born is not consistent for all birth outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The significantly lower rates of gastroschisis among foreign-born women concord with many studies that have observed similarly paradoxical findings of better birth outcomes among foreign-born women, who are typically medically underserved and of lower socioeconomic status. Women born outside the U.S., particularly those of Hispanic ethnicity, have a lower risk of preterm delivery, low birth weight, and infant mortality, and they report less preterm labor and hypertension than U.S.-born women; this advantage tends to diminish with increasing acculturation (Cervantes et al, 1999;Crump et al, 1999;Buekens et al, 2000;Carter-Pokras et al, 2008;McDonald et al, 2008;Ruiz et al, 2008). The protective effect associated with being foreign born is not consistent for all birth outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Many birth outcomes, including infant mortality, low birth weight, and preterm birth, differ according to maternal nativity. Foreign-born women, especially Hispanics, have more favorable birth outcomes than U.S.-born women, despite their having more demographic and socioeconomic risk factors (Crump et al, 1999;Carter-Pokras et al, 2008). Women born outside the United States tend to have more social support, engage in fewer risky behaviors during pregnancy such as tobacco and alcohol use, and have fewer medical risks (Leslie et al, 2006;Campos et al, 2008;McDonald et al, 2008;Ruiz et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is currently no gold standard measure of acculturation; several proxies exist that may assess different constructs of the multidimensional process (7)(8)(9). Prior studies have suggested that the relationship between acculturation and obesity in Hispanics may depend on the specific acculturation measure.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies suggest that family values such as familism and strong social support networks serve as protective factors for Latina/o populations (e.g., Stein, Gonzalez, Cupito, Kiang, & Supple, 2013) and may partially explain the Latina/o immigrant paradox. The protective factor of being an immigrant, however, may come with an expiration date since some studies also suggest that the longer immigrants reside in the U.S., the more their health deteriorates (Carter-Pokras, Zambrana, Yankelvich, Estrada, Castillo-Salgado, & Ortega, 2008). Our efforts to understand Latina/o families' well-being, including those living in rural America, should include research focused on protective factors.…”
Section: Background the Changing Demographics Of Rural Americamentioning
confidence: 99%